2018
DOI: 10.1002/brb3.970
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sleep quality using cardiopulmonary coupling analysis in patients with Parkinson's disease

Abstract: ObjectivesTo assess the sleep quality of patients with Parkinson's disease (PD) and evaluate the effect of cardiopulmonary coupling (CPC) analysis on sleep quality and its correlation with subjective complaints in patients with PD.MethodsOur study included 42 patients with PD and 30 healthy controls. CPC analysis and the Pittsburgh Sleep Quality Index (PSQI) were used to evaluate the sleep quality of subjects.ResultsHigh‐frequency coupling (HFC) and sleep efficiency were significantly lower in the PD than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It was demonstrated that CPC analysis was fit for differentiating and objectively quantifying the sleep quality of insomnia patients (Schramm et al, 2013). The PSQI score showed a negative correlation with the HFC (stable sleep) ratio in PD patients (Chen et al, 2018); however, no correlation was found between the PSQI score and sleep parameters of CPC analysis in insomnia patients.…”
Section: Discussionmentioning
confidence: 98%
“…It was demonstrated that CPC analysis was fit for differentiating and objectively quantifying the sleep quality of insomnia patients (Schramm et al, 2013). The PSQI score showed a negative correlation with the HFC (stable sleep) ratio in PD patients (Chen et al, 2018); however, no correlation was found between the PSQI score and sleep parameters of CPC analysis in insomnia patients.…”
Section: Discussionmentioning
confidence: 98%
“…The CPC technique is based on a continuous single-lead electrocardiogram (ECG) signal to track changes in cardiac inter-beat (R-R) intervals and QRS amplitude during sleep ( 25 ). Since CPC analysis has several advantages, such as objectivity, repeatability, automation, and scorer-independence ( 30 ), it has been widely used to evaluate sleep quality in several diseases, including Parkinson's disease ( 31 ), depression ( 32 ), and obstructive sleep apnea ( 33 ). Therefore, CPC was chosen to measure sleep quality in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The sleep monitoring technology adopted by the wristband is based on an electrocardiogram-based technique named cardiopulmonary coupling technology (CPC; Thomas et al, 2005), which can take exact measurements of sleep patterns, including timing and duration of sleep as well as awakenings (Sadeh, 2011). CPC has been proposed recently as an indicator of sleep stability and as an alternative way of characterising sleep (Thomas et al, 2005), and has been used in some sleep-related studies (Chen et al, 2018;Cysarz et al, 2018;Schramm et al, 2013). Although it cannot replace traditional polysomnography due to imperfect sensitivity and specificity to detect wake periods, this tool can provide reasonable estimates for assessing subjects objectively with minimal participant burden for more prolonged periods of time than conventional assessment tools (Martin and Hakim, 2011).…”
Section: Sleep Quality Measurementsmentioning
confidence: 99%